Host DDX Helicases as Possible SARS-CoV-2 Proviral Factors: A Structural Overview of Their Hijacking Through Multiple Viral Proteins - Squeglia, Flavia; Romano, Maria; Ruggiero, Alessia; Maga, Giovanni; Berisio, Rita (Frontiers in Chemistry, 2020)
As intracellular parasites, viruses hijack the host cell metabolic machinery for their replication. As a consequence, uncovering host-pathogen interactions is the key to understand the molecular basis of viral pathogenicity. Recent studies have revealed a complex network of interactions of coronaviruses proteins, including those of SARS-CoV-2, responsible for the current COVID-19 pandemic, with the host cell proteome. Among other cellular proteins, the DEAD-box (DDX) RNA helicases have been shown to be hijacked by coronaviruses and to participate in essential DDX-mediated viral replication steps. Human DDX RNA helicases play essential roles in a broad array of biological processes and serve multiple roles at the virus-host interface. The viral proteins responsible for DDX interactions are highly conserved among coronaviruses, suggesting that they might play conserved functions also in the SARS-CoV-2 replication cycle. In this review, we provide an update of the structural and functional data of DDX as possible key factors involved in SARS-CoV-2 hijacking mechanisms. We also attempted to fill the existing gaps in the available structural information, through homology modelling. Based on this information, we propose possible ways exploited by the virus to replicate more efficiently by taking advantage of host DDX proteins. As a general rule, sequestration of DDX helicases by SARS-CoV-2 is expected to play a pro-viral role in two ways: by enhancing key steps of the virus life cycle and, at the same time, by suppressing the host innate immune response.